Qualitative Study on Self-Management Experiences of Hypertensive Patients During the Covid-19 Pandemic - Ana Bella; Sutantri Sutantri (Universitas Aisyah Pringsewu, 2022)
High blood pressure, often known as hypertension, is a chronic condition that if left untreated can lead to problems such as kidney failure, heart disease, stroke and other serious illnesses. People with co-morbidities are one of the populations that are most susceptible to contracting the virus during the Covid-19 (Coronavirus Disease 2019) pandemic. According to the Ministry of Health 2020, hypertension made up 50.5 percent of the comorbidities. Self-management is the foundation to be able to manage hypertension and preventing its complications. However, during the Covid-19 pandemic, it can have an impact on the management of chronic diseases such as hypertension because it is caused by a number of factors in efforts to prevent the transmission of Covid-19. The purpose of this study to determine the experience and application of self-management in hypertensive patients during the Covid-19 pandemic. The qualitative descriptive method is used in this study. This study had 9 participants who were chosen using a purposive sampling technique. According to the findings, three themes can be used to explain how hypertensive patients experienced self-management during the Covid-19 pandemic; Not being affected by the pandemic, Disrupted self-management, and Contextual factors influencing self-management during the Covid-19 pandemic. Self-management of hypertensive patients did not change much before and during the pandemic, although treatment was changed during the Covid-19 outbreak. Due to the support of families, medical personnel, and health resources, people with hypertension can still manage themselves efficiently during the Covid-19 pandemic. Abstrak: Tekanan darah tinggi, yang sering disebut dengan hipertensi, adalah kondisi kronis yang jika tidak ditangani dapat menyebabkan masalah seperti penyakit jantung, gagal ginjal, stroke, dan penyakit serius lainnya. Orang dengan penyakit penyerta adalah salah satu populasi yang paling rentan tertular virus selama pandemi Covid-19 (Coronavirus Disease 2019). Menurut Kementerian Kesehatan 2020, hipertensi merupakan 50,5 persen dari penyakit penyerta. Self-management merupakan landasan untuk dapat mengelola hipertensi dan mencegah komplikasinya. Namun, di masa pandemi Covid-19 dapat berdampak pada pengelolaan penyakit kronis seperti hipertensi karena disebabkan oleh sejumlah faktor dalam upaya pencegahan penularan Covid-19. Tujuan penelitian ini untuk mengetahui pengalaman dan penerapan self-management pada pasien hipertensi pada masa pandemi Covid-19. Metode deskriptif kualitatif digunakan dalam penelitian ini. Penelitian ini memiliki 9 partisipan yang dipilih dengan menggunakan teknik purposive sampling. Hasil penelitian didapatkan tiga tema yang dapat digunakan untuk menjelaskan bagaimana pasien hipertensi melakukan manajemen diri selama pandemi Covid-19 yaitu; Tidak terpengaruh pandemi, Self-management terganggu, Faktor kontekstual mempengaruhi manajemen diri selama pandemi Covid-19. Self-management pasien hipertensi tidak banyak berubah sebelum dan selama pandemi, meskipun pengobatan diubah selama wabah Covid-19. Adanya dukungan keluarga, tenaga medis, dan sumber daya kesehatan, penderita hipertensi tetap dapat mengelola diri secara efisien di masa pandemi Covid-19.